Dual-task walking on real-world surfaces: Adaptive changes in walking speed, step width and step height in young and older adults - Charlotte Hennah; Michail Doumas (Experimental Gerontology, 2023)
Objectives: Age-related changes in dual-task walking are well established, but research in this topic is based on evidence from laboratory rather than real-world studies. We investigated how dual-task walking on real-world surfaces affects young and older adults' gait characteristics and cognitive resource allocation. Method: Sixteen young (aged 19–35, 12 female) and fifteen older adults (aged 70–85, 7 female) with no major neurological or musculoskeletal disorders walked at a self-selected speed on forty-metre outdoor paths that had asphalt or grass surface. They walked with or without a cognitive task (counting backwards). Cognitive task difficulty was individually adjusted at 80 % accuracy. Participants performed the three tasks in Single Task (ST Asphalt, ST Grass, ST Cognitive) and Dual Task context (DT Asphalt-Cognitive, DT Grass-Cognitive). Results: The two groups showed similar dual task effects in cognition and walking speed, both of which were slower when dual-task walking. Older adults' steps were wider overall but only young adults widened their step width when dual-task walking on grass compared to asphalt. Similarly, young adults' step height increased from single to dual-task walking when on grass, where older adults' did not. Discussion: The lack of adaptation of step width and height when dual-task walking may leave older adults vulnerable to tripping or falling in common real-world conditions, such as while walking on grass, gravel, or uneven city sidewalks. Considering this, the built environment should be made more accessible to facilitate older adults' safe walking.